A Perspective Review of Cancer Therapy (Part I): Immunotherapy, Gene Therapy, and Nanotechnology - Pajuelo, Alberto (Science Insights, 2023)
The application of genomic profiling approaches has propelled the advancement of precision medicine, enabling the development of personalized treatment programs that are specifically customized for each particular patient. This method considers the distinct genetic composition of each tumor, allowing for the detection of crucial driver mutations and possible weaknesses that might be targeted for therapeutic purposes. Furthermore, immunotherapy has emerged as a promising approach in cancer treatment, utilizing the potential of the immune system to identify and eradicate cancerous cells. Medical breakthroughs like CAR-T cell therapy have already demonstrated exceptional efficacy in treating hematologic malignancies. Moreover, state-of-the-art technologies such as CRISPR-Cas9 gene editing offer potential for directly altering tumor cells or augmenting the efficacy of current treatments. The future of cancer therapy is focused on developing more precise and targeted techniques to enhance patient outcomes and ultimately overcome this destructive illness. This involves continual research and cooperation among scientists, physicians, and pharmaceutical corporations on a worldwide level.